912. Beyond the Usual Suspects in Invasive Mold Infections: Public Health Surveillance Identifies Clinical Diversity. (31st December 2020) - Beer, Karlyn; Kelly, Hilary; Blakney, Rebekah; Revis, Andrew; Perry, Lewis; Bentz, Meghan; Berkow, Elizabeth L; Lockhart, Shawn R; matkovic, Eduard; Thomas, Stepy; Oliver, Nora; Webster, Andrew; et al.
Abstract: Background: Invasive mold infections (IMI) such as aspergillosis and mucormycosis are often fatal among immunocompromised patients and cause high-profile outbreaks. Public health surveillance for IMI is challenging; most epidemiologic studies are limited to transplant and cancer patients at greatest risk of IMI. The established Mycoses Study Group (MSG) case definition is useful for clinical trials but lacks sensitivity. To address these challenges, we created IMI surveillance within the Georgia Emerging Infections Program. Here, we describe cases identified through this system, using both the MSG criteria and a novel, more sensitive surveillance case definition. Methods: To identify potential IMI cases, we captured 2, 363 positive fungal laboratory results, including cultures, histopathology, and galactomannan tests, within a 60-day window at three large Atlanta hospitals during April 2018–March 2019. We excluded yeast and dimorphic fungi, hair and nail specimens, and cystic fibrosis patients. Potential cases underwent chart review and were classified by 2 physicians as proven, probable, or non-case according to MSG criteria. Cases that partially met MSG probable criteria and included antifungal treatment were classified as surveillance cases; definitions were mutually exclusive (Fig 1). Results: Of 120 potential IMI cases, 46 (38%) met an IMI case definition: 8 proven, 9 probable, and 29 surveillance cases (Fig 2). Of cases, 14 (30%) involved transplant or cancer in the previous year; 8 of these were proven or probable cases. IMI presented primarily as sinusitis among proven cases (50%), and pulmonary infections among probable (56%) and surveillance (45%) cases. Most surveillance cases were caused by Aspergillus spp. (72%) and accounted for all 5 cutaneous IMI (fig 3). Over 80% of cases vs. 10% of non-cases had antifungal treatment. Conclusion: Of IMI cases identified, nearly two thirds had evidence of infection but did not meet an MSG case definition. MSG captured over half of transplant and cancer-associated cases, but these were uncommon overall, revealing most IMI lack classical risk factors. A more sensitive surveillance case definition can capture a broader spectrum of IMI patients receiving antifungal treatment to help guide clinical and public health interventions. Disclosures: All Authors : No reported disclosures